Strategi Komunikasi Orang Tua dan Guru Dalam Membentuk Karakter Religius pada Siswa SDN 10 Mentok - Septi Dewi Anggraini (Al-Qolamuna: Journal Komunikasi dan Penyiaran Islam, 2025)
The implications of effective communication strategies between teachers and parents have a positive impact on the formation of students' religious character within the school and family environment. Synergy between the two facilitates monitoring of students' behavior and academic development and strengthens the internalization of religious values. This study recommends increased communication collaboration between teachers and parents as a key to successfully developing students' religious character. This study aims to examine the communication strategies used by teachers and parents in developing religious character in students at Mentok 10 Public Elementary School. Religious character is an important foundation for creating a generation with noble morals and strong faith. This study used a qualitative approach with a case study method and was conducted at Mentok 10 Public Elementary School from July to August 2025. Data were obtained through observation, in-depth interviews, and documentation with informants including religious teachers, students, and parents. The results indicate that communication strategies between teachers and parents are implemented both directly and indirectly. Direct communication includes parent visits to the school, the formation of a school committee, parent-student associations, and report card collection. Indirect communication is conducted through digital media such as WhatsApp groups for information exchange and monitoring of students' religious character development. The religious character of students at SD Negeri 10 Mentok is reflected in their daily prayer habits, disciplined recitation of the Quran, congregational prayer, honesty, sincerity, self-confidence, creativity, responsibility, love of knowledge, discipline, obedience to rules, tolerance, and respect for others. Abstrak Implikasi strategi komunikasi yang efektif antara guru dan orang tua berdampak positif pada pembentukan karakter religius siswa di lingkungan sekolah dan keluarga. Sinergi antara keduanya mempermudah pengawasan perilaku dan perkembangan akademik siswa serta memperkuat internalisasi nilai-nilai agama. Penelitian ini merekomendasikan peningkatan kerja sama komunikasi antara guru dan orang tua sebagai kunci keberhasilan pembentukan karakter religius siswa. Penelitian ini bertujuan untuk mengkaji strategi komunikasi yang digunakan oleh guru dan orang tua dalam membentuk karakter religius pada siswa Sekolah Dasar Negeri 10 Mentok. Karakter religius merupakan fondasi penting dalam menciptakan generasi yang berakhlak mulia dan memiliki keimanan yang kuat. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus yang dilakukan di SD Negeri 10 Mentok selama bulan Juli hingga Agustus 2025. Data diperoleh melalui observasi, wawancara mendalam, dan dokumentasi dengan informan berupa guru agama, siswa, dan orang tua siswa. Hasil penelitian menunjukkan bahwa strategi komunikasi antara guru dan orang tua dilakukan secara langsung dan tidak langsung. Komunikasi langsung mencakup kunjungan orang tua ke sekolah, pembentukan komite sekolah, paguyuban orang tua siswa, dan pengambilan raport. Komunikasi tidak langsung dilakukan melalui media digital seperti grup WhatsApp untuk pertukaran informasi dan pengawasan perkembangan karakter religius siswa. Karakter religius siswa di SD Negeri 10 Mentok tercermin dalam kebiasaan doa sehari-hari, disiplin mengaji, pelaksanaan sholat berjamaah, sikap jujur, ikhlas, percaya diri, kreatif, bertanggung jawab, cinta ilmu, disiplin, taat peraturan, toleransi, dan penghormatan terhadap orang lain.